Renewable Energy Integration in Maritime Infrastructure : Qualitative Study of IMO Documents - Jabbie, Fatoumata (My University, 2024)
The shipping industry is an estimated 3 percent contributor to global GHG emissions; it remains, however, a critical link to world trade, shipping about 80% of the goods consumed worldwide, including a large part of the basic supplies of food and medicine (Bouman et al., 2017; UNCTAD, 2022). On the other hand, despite the setting of ambitious targets by IMO for at least a 50 percent reduction in its emissions before the middle of this century, its uptake into industry has been very slow concerning of renewable energy technologies and alternative fuels (Smith et al., 2021). This research addresses three key questions: (1) How is the IMO addressing the integration of renewable energy in maritime operations? (2) What are the key challenges and solutions for integrating renewable energy within the sector? (3) How do actual industry practices compare to the IMO’s recommendations? To answer these questions, the study draws on a thorough review of literature and an analysis of IMO documents and policies. Findings reveal that while the IMO has set a robust framework through initiatives such as the “Energy Efficiency Design Index (EEDI)” and the “Carbon Intensity Indicator (CII)”, several barriers hinder the maritime industry’s full shift to renewable energy. These include high upfront investment costs, technological limitations, and a lack of infrastructure to support alternative fuels like hydrogen and ammonia. Although energy efficiency improvements have been widely adopted, the move towards renewable energy has been slow and uneven across the industry. The research concludes that stronger international collaboration, enhanced financial incentives, and strategic investments in infrastructure are required to accelerate Maritime’s alignment with the IMO’s decarbonization objectives. This thesis gives great insights for policymakers and industry leaders looking to close the gap between policy and practice and to drive the transition toward a sustainable maritime future.
Keywords: Renewable Energy, Maritime Transport, International Maritime Organization (IMO), Greenhouse Gas Emissions, Decarbonization, Alternative Fuels, Carbon Neutrality, Zero-emission Fuels, Fossil Fuels, Sustainable Energy Transition